Характеристика відмов елементів водопостачання для систем крапельного зрошення - Журавель, Дмитро Павлович; Пастушенко, Сергій Іванович; Артьомов, Микола Прокопович; Волинкін, Микола Петрович; Zhuravel, Dmytro; Pastushenko, Serhii; Artomov, Mykola; Volynkin, Mykola (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті проведено системний аналіз досліджень відмов елементів водопостачання систем зрошення. Розглянуто основні типи відмов насосних станцій, трубопроводів, фільтраційних вузлів, краплинних ліній та систем автоматизації. Проаналізовано причини виникнення відмов, їх вплив на ефективність функціонування зрошувальних систем та методи оцінювання надійності. Встановлено ключові фактори, що визначають інтенсивність відмов, зокрема якість води, гідравлічні режими та рівень технічного обслуговування. Запропоновано напрями підвищення експлуатаційної надійності систем водопостачання. /// EN: Тhe article conducts a systematic analysis of studies of failures of water supply elements of irrigation systems. The main types of failures of pumping stations, pipelines, filtration units, drip lines and automation systems are considered. The causes of failures, their impact on the efficiency of irrigation systems and methods for assessing reliability are analyzed. Key factors that determine the intensity of failures are identified, in particular water quality, hydraulic modes and the level of maintenance. Directions for increasing the operational reliability of water supply systems are proposed. The stability of irrigation systems directly depends on the trouble-free operation of water supply elements – water intake structures, pumping stations, pressure and distribution pipelines, filtration equipment, shut-off and control valves and automation equipment. Failure of at least one of these components leads to a decrease in pressure and water consumption, uneven irrigation, excess electricity consumption, emergency downtime and, as a result, to a decrease in crop yields and economic losses. At the same time, a significant part of existing irrigation systems is characterized by a high degree of physical and moral wear and tear, which increases the likelihood of failures and complicates the provision of stable hydraulic modes. Hidden defects in pipelines, corrosion processes, cavitation phenomena in pumping equipment, water hammer, as well as clogging of filtration elements due to low water quality are of particular danger. Insufficient level of automation and technical diagnostics leads to untimely detection of malfunctions and transition of local defects into large-scale accidents. Despite the existence of separate studies in the field of reliability theory and operation of hydraulic systems, the issues of comprehensive assessment of the reliability of irrigation water supply systems remain insufficiently developed, in particular in terms of taking into account real operating conditions, variable loads and the impact of water quality on the durability of equipment. There is a need to improve methods of predicting failures, determining the intensity of their occurrence, assessing indicators of failure-freeness, durability and maintainability, as well as developing scientifically based recommendations for increasing the availability coefficient of systems.
Failure characteristics of water supply elements for drip irrigation systems
Keywords: інтенсивність відмов; насосні станції; трубопроводи; краплинне зрошення; водопостачан- ня; надійність; гідравлічні режими; технічне обслуговування; failure rate; pumping stations; pipelines; drip irrigation; water supply; reliability; hydraulic modes; maintenance